The Effect of Compensation and Work Environment on Employee Performance at PT. Mustika Ratu Tbk, Ciracas-East Jakarta - Napitupulu, Hotma; Winarto, Herry (Technium Social Sciences Journal, 2021)
This study aims to determine and analyse the Effect of Compensation, Work Environment on Employee Performance at PT. Mustika Ratu Tbk, Ciracas - East Jakarta. This research was conducted using a sample of 92 employees of PT. Mustika Ratu. The data collection technique used was by spreading questionnaires. The data analysis technique used is descriptive analysis and multiple linear regression analysis. The results of the study using multiple linear regression analysis showed that simultaneously (F test) the compensation and work environment variables had a positive and significant effect on the employee performance variable of PT. Mustika Ratu Tbk, Ciracas-East Jakarta. As for the (t-test) of these results, it turns out that the compensation variable has a positive and significant effect on the employee performance of PT. Mustika Ratu Tbk, Ciracas-East Jakarta and the Work Environment variable has a positive and significant effect on the Employee Performance of PT. Mustika Ratu Tbk, Ciracas-East Jakarta.